THE IMPACT OF ECONOMIC GROWTH, FERTILITY AND THEIR CONSEQUENCES ON RESOURCE USE IN PROJECTING DEMAND FOR EDUCATION IN MALAYSIA - Gan, Pei Tha (International Business Education Journal, 2008)
Population structures and population increase have been one of the major concerns of not only policy makers of developing nation but also the world at large such as UNDP. Economic development and economic activity have been closely associated with population growth. The basic objective of any government has been catering for its citizens. Rapid increase in population may deplete the country’s resources thereby inviting the dreaded onset of depression and inflation. Factors affecting population growth have been considered as important elements in economic planning in most countries including Malaysia. Unplanned population growth all adversely affects resources use as well as creates insatiable demand particularly for education. This study attempts to investigate the fields of natality (fertility), economic growth and contribution of education indicator as a parsimonious model. Basically, this study tested the postulate that population growth (birth rates) is positively associated with increasing mortality rates and later followed by declining in mortality rates. The study also shed light on the essentials of the relation between economic growth and population growth (birth rates). Using recently applied econometrics techniques, namely ARDL bounds test based on UECM proposed by Pesaran et al. (2001), and the long-run Granger non-causality popularized by Toda-Yamamoto (1995), the model was significant in investigating the contributions of natality, growth and education in Malaysia. The significance of the model indicated strong policy implications with regard to future planning of education requirements in the country.